Radiological characterization of the ancient Roman tuff-pozzolana underground quarry in Orvieto (Italy): A natural laboratory to revisit the interactions between radionuclides and aerosols. (March 2017) - Nuccetelli, C.; Trevisi, R.; Leonardi, F.; Ampollini, M.; Cardellini, F.; Tonnarini, S.; Kovler, K.; Vargas Trassiera, C.
Abstract: Orvieto (Italy) has a large network of underground tunnels quarried to extract tuff and pozzolana by Etruscans and Romans. One of these tunnels was chosen as natural laboratory to compare different radiation measurement and dose assessment methods. Indeed, tuff and pozzolana are very rich in natural radioactivity and are interesting from the radiation protection point of view since they are still used as building materials. In order to characterize this site an in situ experimental procedure was followed. It consisted in measurements carried out with different instruments: two portable gamma ray spectrometers, two gamma dose rate meters, two radon monitors and one two channel working level monitor. Samples of tuff and pozzolana stones were also collected to be measured with gamma spectrometry in laboratory. Due to the high content of 238 U, 232 Th (more than 200 Bq kg −1 for both radionuclides) and 40 K (more than 2000 Bq kg −1 ) of tuff and pozzolana, elevated levels of exposure to natural radioactivity were found: indeed, with different instruments and approach, a gamma dose rate of about 1 μGy h −1 and an average radon concentration of about 10, 000 Bq m −3, with a Potential Alpha Energy Concentration (PAEC) of 288 MeV cm −3, were measured. The radiological characteristics of Orvieto underground quarry make it a perfect site for "in field" intercomparisons of different measurement and dose assessment methods. Highlights: An underground quarry as a natural laboratory to test dose assessment methods. Eight different monitors used. Tuff and pozzolana stones measured with gamma spectrometry in laboratory. High activity concentrations of natural radionuclides were found.